KAJIAN TEKNIK BUDIDAYA TANAMAN CABAI (Capsicum annuum L.) KABUPATEN MINAHASA TENGGARA - Polii, M. G. M.; Sondakh, T. D.; Raintung, J. S. M.; Doodoh, Beatrix; Titah, Tilda (Universitas Sam Ratulangi, 2019)
Chili is a strategic commodity with important economic value in Indonesia. The Ministry of Agriculture included chili in a special program as of 2015 to increase production. Chili as a commodity has a high impact on Indonesia’s economy, party because fluctuations in its price can influence inflation. Data from the Central Statistics Agency indicate that chili supplies decrease during the rainy season while demand increases in the months of Ramadhan, Christmas, and New Year, and in these times chili prices increase and cause inflation. To support national demand, there needs to be an increase in chili productivity. Chili plots sometimes cannot be planted year-round due to the high use of artificial chemical fertilizer with excessive dosage, thus decreasing the quality of land and quality and volume of chili crop yield. For that reason, there needs to be a study that identifies cultivation techniques for chili in the regency of Southeast Minahasa. Study results show that cultivation methods in Molompar village, Southeast Minahasa, still depends on farmers’ experiences. Field instructors have not been optimally guiding the local farmers.